2012
DOI: 10.3233/wor-2012-1347
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the implementation of a comprehensive intervention programme on premature discharge outcomes from military training

Abstract: Objective: The study describes and analyses the influence of a comprehensive intervention on premature discharges (i.e. the military training cannot be completed). Participants: 862 male soldiers from three military units were included. Methods: The intervention included a screening protocol with a questionnaire and physical tests for musculoskeletal complaints or injuries and functional limitations and, where needed, treatment, early rehabilitation and individually-adjusted physical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Another reason for including this test was earlier findings indicating that a lack of strength correlated with pain in the lower back (i.e. shorter maximal contraction times and functional disability) [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for including this test was earlier findings indicating that a lack of strength correlated with pain in the lower back (i.e. shorter maximal contraction times and functional disability) [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, different versions of the Army Physical Fitness Test that only uses the soldiers own body weight when performing sit-ups and push-ups [ 5 ] may be considered inappropriate, since soldiers’ work tasks further require them to carry external loads [ 6 , 9 , 12 , 14 ]. Although research has shown that data obtained from physical tests can be used independently to predict future injury occurrence [ 2 , 15 17 ] or physical performance [ 14 , 18 20 ], the content validity of these tests are often not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-seven studies underwent phase II full-text screening. Sixteen relevant studies [2944] were identified (eight observational studies including case reports and series, cross-sectional and non-experimental studies, and cohorts; four mixed methods studies; three pilot studies; one qualitative study). Fourteen studies were conducted in the US, and one study each was conducted in Canada and Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Os militares, principalmente os alunos de cursos de operações especiais, devem estar aptos a realizarem diversos tipos de exercícios físicos, muitas vezes sob condições adversas (excesso de calor e umidade, privação de sono, hidratação e alimentação restrita), o que é inerente à atividade. Entretanto, em especial nas fases básicas, iniciais ou preparatórias, a realização de um controle de cargas e a implementação de um programa educacional a respeito de hábitos posturais, hidratação e ergonomia podem contribuir para a prevenção de lesões musculoesqueléticas 47 .…”
Section: Recomendaçõesunclassified